Paramagnetic collective electronic mode and low temperature hybrid modes in the far infrared dynamics of orthorhombic NdMnO3 - Massa, Nestor Emilio (2013)
We report on the far- and mid-infrared reflectivity of NdMnO3 from 4 to 300 K. Two main features are distinguished in the infrared spectra: active phonons in agreement with expectations for the orthorhombic ${D}_{2h}^{1 6}$–Pbnm (Z = 4) space group remaining constant down to 4 K and a well defined collective excitation in the THz region due to eg electrons in a d-orbital fluctuating environment. We trace its origin to the NdMnO3 high-temperature orbital disordered intermediate phase not being totally dynamically quenched at lower temperatures. This results in minute orbital misalignments that translate into randomized non-static eg electrons within orbitals yielding a room-temperature collective excitation. Below TN ~ 78 K, electrons gradually localize, inducing long-range magnetic order as the THz band condenses into two modes that emerge pinned to the A-type antiferromagnetic order. They harden simultaneously down to 4 K, obeying power laws with TN as the critical temperature and exponents β ~ 0.25 and β ~ 0.53, as for a tri-critical point and Landau magnetic ordering, respectively. At 4 K they match known zone center spin wave modes. The power law dependence is concomitant with a second order transition in which spin modes modulate orbital instabilities in a magnetoelectric hybridized orbital–charge–spin–lattice scenario. We also found that phonon profiles also undergo strong changes at TN ~ 78 K due to magnetoelasticity.